The Role of Endoplasmic Reticulum in the Differential Endurance against Redox Stress in Cortical and Spinal Astrocytes from the Newborn SOD1G93A Mouse Model of Amyotrophic Lateral Sclerosis - Cecilia Marini; Vanessa Cossu; Mandeep Kumar; Marco Milanese; Katia Cortese; Silvia Bruno; Grazia Bellese; Sonia Carta; Roberta Arianna Zerbo; Carola Torazza; Matteo Bauckneht; Consuelo Venturi; et al. (MDPI AG, 2021)
Recent studies reported that the uptake of [18F]-fluorodeoxyglucose (FDG) is increased in the spinal cord (SC) and decreased in the motor cortex (MC) of patients with ALS, suggesting that the disease might differently affect the two nervous districts with different time sequence or with different mechanisms. Here we show that MC and SC astrocytes harvested from newborn B6SJL-Tg (SOD1G93A) 1Gur mice could play different roles in the pathogenesis of the disease. Spectrophotometric and cytofluorimetric analyses showed an increase in redox stress, a decrease in antioxidant capacity and a relative mitochondria respiratory uncoupling in MC SOD1G93A astrocytes. By contrast, SC mutated cells showed a higher endurance against oxidative damage, through the increase in antioxidant defense, and a preserved respiratory function. FDG uptake reproduced the metabolic response observed in ALS patients: SOD1G93A mutation caused a selective enhancement in tracer retention only in mutated SC astrocytes, matching the activity of the reticular pentose phosphate pathway and, thus, of hexose-6P dehydrogenase. Finally, both MC and SC mutated astrocytes were characterized by an impressive ultrastructural enlargement of the endoplasmic reticulum (ER) and impairment in ER-mitochondria networking, more evident in mutated MC than in SC cells. Thus, SOD1G93A mutation differently impaired MC and SC astrocyte biology in a very early stage of life.